THE IMPACTS OF THE COMMON CONSOLIDATED CORPORATE TAX BASE IN CROATIA (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
As of 1 July 2013, i.e. with Croatia’s accession to the European Union, the number of Member States of the European Union rose to 28. The diversity of tax systems among the Member States causes interferences in cross-border activities of tax firms. That encourages transfer of income to countries with lower tax rates. The aim of this paper is to present the main points of view on the implications of the introduction of the Common Consolidated Corporate Tax Base (CCCTB) in Croatia. This paper also estimates the effects of the prospective apportionment procedure on corporate group entities in Croatia. The acceptance of the CCCTB system will make Croatia attractive to foreign investors. It will also enable foreign multinational companies to do business in Croatia, which will contribute to its economic growth. Keywords: Fiscal policy, corporate income tax, common consolidated corporate tax base, formula apportionment